Pengembangan Media Permainan Edukatif Jenga Pintar (Jetar) Tema Ekosistem Untuk Meningatkan Minat Belajar Peserta Didik Sekolah Dasar - Khasanah, Sholekhah Nur; Hendracipta, Nana; Andriana, Encep (Universitas Muhammadiyah Magelang, 2023)
The aim of this research and development is to understand the process of developing the educational game media Jenga Smart with the ecosystem theme, its feasibility, student responses, and the students' learning interest after using this media. This media contains content related to thematic learning, specifically Theme 5